MANAGEMENT OF THE WORK PROCESS IN HEALTH CARE ORGANIZATION: WELCOME IN PRIMARY CARE - Eleandro Costa, Farley; Costa Lopes, Marden; Paiva dos Santos Rocha, Silvânia; Xavier da Silva, Rosilaine; Souza Santos de Sá, Daniela; Julliana Costa Diniz, Héllen; Caroline Silva Santiago, Jéssica; Costa Aquino Pereira, Talita; Soares Santos Brandão, Silvânia; de Brito Oliva Dias, Cássia; Caroline Oliveira de Souza Boitrago, Sarah; Alves dos Santos, Nandeiara; et al. (Health and Society, 2026)
OBJECTIVE: To describe the welcoming process in primary health care as a strategy for managing the work process. METHOD: The research was conducted through an integrative review, using the LILACS, SCIELO, and BDENF databases, with the descriptors welcoming, primary health care, work process management, people management, and multidisciplinary team. RESULTS: It was found that the actions conceived as welcoming are carried out in specific shifts and times, by a professional category, considered as triage of acute complaints that would determine medical care. CONCLUSION: Most professionals have little understanding or are unaware of the guidelines of the National Humanization Policy and the expanded concept of welcoming, generating work processes incompatible with the policy, resulting in several challenges to be faced by the team. Thus, they must believe in the organization of welcoming as an indispensable practice for improving work management in primary care, enabling more humanized and effective care.